Nanoparticles in the Treatment of Infections Caused by Multidrug-Resistant Organisms - Lee, Nan-Yao; Ko, Wen-Chien; Hsueh, Po-Ren (Frontiers in Pharmacology, 2019)
Nanotechnology, the use of materials with dimensions on the atomic or molecular scale, has become increasingly utilized for medical applications and is of great interest as an approach to kill or reduce the activity of numerous microorganisms. Infections caused by multidrug-resistant organisms (MDROs) are emerging causes of morbidity and mortality worldwide. The optimal treatment route for infections caused by MDROs is often unclear, and the antibiotic options are limited. These challenges highlight the critical demand for alternative and effective antimicrobial strategies. The physical structure of a nanoparticle itself and the way in which it interacts with and penetrates into bacteria appear to provide unique bactericidal mechanisms. Coupling nanoparticles and natural-based antimicrobials (or other repurposed compounds) to inhibit bacterial efflux pumps, biofilm formation, quorum sensing, and possibly plasmid curing, are some of the strategies to combat MDROs. Combinatorial therapy with metallic nanoparticles, as an adjunct to existing antibiotics, may aid in restraining the mounting menace of bacterial resistance. In this review, we will summarize the current researches on nanoparticles and other nanomaterials and how they are applied or can be applied in the future to fight MDROs.